Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievment Division Terhadap Penguasaan Kompetensi Pengetahuan IPS - Utami, Ni Putu Adi; Asri, I G.A. Agung Sri; Negara, I Gusti Agung Oka (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to determine the differences of cooperative learning model of Student Teams Achievment Division (STAD) type and conventional learning on the competence of IPS knowledge of fourth grade students of SD Negeri Gugus Pattimura of the academic year 2016/2017 on the theme of Kayanya Negeriku. This study is an experimental study to compare IPS knowledge competence which is taught by cooperative learning model of STAD type and students who are taught by conventional learning using scientific approach. The research design used is a quasi-experimental design with noquivalent control group design. The population in the study were all fourth grade students of SD Negeri Gugus Pattimura. Sampling technique using randoms sampling then conducted equality test on the sample. Then proceed with a prerequisite test that obtains the result that the sample group is normally distributed and has a homogeneous variance. After the prerequisite test, the hypothesis test is done with the criterion tcount ≤ ttable at 5% significance level and dk = 38 + 40 - 2 = 76 is 2.00. Based on result of hypothesis test obtained tcount = 2,64, then result of tcount compared with ttable that get result tcount > ttable. The conclusion of this research is that there is a significant difference in the mastery of IPS knowledge competence of the group of students who are taught using STAD type cooperative learning model and the group of students who are taught using conventional learning.